Kajian Tentang Maklum Balas Masyarakat Terhadap Aktiviti Masjid-masjid Negeri di Semenanjung Malaysia - Md. Yusoff, Yusmini; Sulaiman, Mohd Anwarulhaq (Jurnal Usuluddin, 2004)
This article attempts to identify the effectiveness of states mosque activities in Peninsular Malaysia. It based on findings, which are done through survey research in term of Muslim perception to the various types of activities organized by the mosques. The data that have been collected were analyzed by using the Statistical Package for Social Science. The result of the study shows that most of respondent are satisfied with the activities.